The Idea of The Muslim World, A Global Intellectual History - Maulana, Moch Dimas (Islamic Studies Review, 2023)
The Idea of The Muslim World, A Global Intellectual History | Cemil Aydin | London: Harvard University Press, 2017. The notion of "The Muslim World" as a binary point of opposition to "The West" has become a global narrative, accepted by many Muslims and non-Muslims alike. In fact, Muslims reside in different parts of the world, speak different languages, live in different traditions and cultures, and have different nationalities and political interests. Besides, the those who believe in notions of the Muslim world have rarely discussed or imagined the Christian world, the Buddhist world, and so on in similar terms. Thus, how did this narrative about the 'Muslim World' come into being and become a mainstream belief in the modern world? This issue constitutes the main point of discussion in Cemil Aydin's book, as the title suggests, "The Idea of The Muslim World." Questions such as who, when, how, and why this notion arose and persists in the modern era are discussed.